Evaluation of The Biochemical Contents in Guillard f/2 and Walne Growth Medium to Fulfill the Animal-Free Aspects of Microalgal Bioprocessing - Stiawan, Elva (Indonesian Scholar Society, 2022)
Marine microalgae with their diverse biomolecule contents could be used as potential sources of food, cosmetics, and pharmaceutical ingredients. In accordance with regulations in some countries and to competitively engage huge numbers of consumers, microalgae-based products should be properly manufactured using non-animal-derived materials. As a cultivable microorganism using a scalable bioreactor technique, consideration of the origin of the material used in the upstream process of marine microalgae was inevitable. Currently, the material origin of chemical contents within common artificial microalgal seawater medium had not been evaluated. This article evaluated Guillard f/2 and Walne medium as common artificial microalgal nutrients used in marine microalgal bioprocess-related activities. The risk assessment results showed that the largest portion of Guillard f/2 and Walne media were inorganic salts considered as low, while the remaining biochemical contents of vitamins were categorized as high risk due to their relatively complex chemical synthesis and enzymatic stages during the manufacturing process. As a suggestion, several plant-based bioproducts were proposed as alternative sources to substitute related biochemical actions to fulfill non-animal-origin aspects in the initial stages of the bioprocessing of marine microalgal-based products.